1993
DOI: 10.1093/jnci/85.11.902
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of c-myc Amplification to Progression of Breast Cancer From In Situ to Invasive Tumor and Lymph Node Metastasis

Abstract: These results suggest that c-myc amplification can occur at an early stage in tumor progression and that amplification does not always persist in the nodal metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 0 publications
2
36
1
4
Order By: Relevance
“…Our data suggest that the three regions of amplification are not involved in the process by which cells acquire metastatic capacity. Our findings are in agreement with those of Watson et al (1993), who suggested that MYC gene amplification can occur at an early stage of tumour progression and does not always persist in nodal metastases. Taken together, the results of this latter study and of our own study suggest that MYC (and also ERBB2) amplification plays a major role in the development of primary breast cancer but not in the distant spread of tumour cells.…”
Section: Discussionsupporting
confidence: 93%
“…Our data suggest that the three regions of amplification are not involved in the process by which cells acquire metastatic capacity. Our findings are in agreement with those of Watson et al (1993), who suggested that MYC gene amplification can occur at an early stage of tumour progression and does not always persist in nodal metastases. Taken together, the results of this latter study and of our own study suggest that MYC (and also ERBB2) amplification plays a major role in the development of primary breast cancer but not in the distant spread of tumour cells.…”
Section: Discussionsupporting
confidence: 93%
“…Amplification data in Champeme et al (1994), Scorilas et al (1995) and Berns et al (1992) were excluded from estimation of the overall proportion, since they were originally reported in Bieche et al (1994), Scorilas et al (1993) and Berns et al (1992b), respectively. Of the 29 reports, 26 determined c-myc amplification by Southern blot, three by slot blot (Tsuda et al, 1989;Zhou et al, 1989;Borg et al, 1992), and two by polymerase chain reaction (Watson et al, 1993;Lonn et al, 1995). Two studies utilized more than one method (Zhou et al, 1989;Lonn et al, 1995).…”
Section: Results Of Citation Searchmentioning
confidence: 99%
“…However, subsequent reports containing new data on prognostic factors or survival were also incorporated into pooled analyses of the specific clinical end-points. Data from studies that used more than one method to determine the overall frequency of amplification were included separately in subgroup analyses of the individual methods (Zhou et al, 1989;Watson et al, 1993). Consideration of methodologic aspects included the sources of tissue and amplification controls, specification of the positive threshold for gene amplification, and a description of the characteristics of the study population (Trock et al, 1997).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of Myc proteins is deregulated in approximately one-third of human cancers through a variety of mechanisms (Cole, 1986;Kelly and Siebenlist, 1986;Spencer and Groudine, 1991). Overexpression of Myc is especially common in certain advanced cancers, such as hormone-independent adenocarcinomas of the breast and prostate, where it is associated with poor prognosis (Berns et al, 1992;Borg et al, 1992;Hehir et al, 1993;Kreipe et al, 1993;Shiu et al, 1993;Watson et al, 1993;Strohmeyer and Slamon, 1994;Bova and Isaacs, 1996;Cher et al, 1996;Jenkins et al, 1997). However, since deregulation is su cient for oncogenic activation, the involvement of Myc in late stage cancers may be even broader than suggested by these studies.…”
mentioning
confidence: 99%